2010
DOI: 10.1111/j.1863-2378.2009.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Emergence of West Nile Virus in Italy

Abstract: In August 2008, West Nile disease re-emerged in Italy. The infection is affecting the North Eastern regions and, as of November 2008, has caused 33 clinical cases and five fatalities in horses. Until now, no deaths have been reported in birds. Mosquitoes, blood, serum and tissue samples, from horses and birds, within and around the outbreak area, have been collected and tested by various methods both serologically and virologically. West Nile virus strains have been isolated from blood samples of one horse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…In order to monitor and control WNV 55 circulation, a serological, entomological and virological surveil-56 lance program for West Nile neuroinvasive disease has been imple-57 mented at the national level by the Italian Ministry of Health 58 (Italian Ministry of Health, 2008). Within this framework it was 59 possible to detect viral circulation in birds, mosquitoes and equids 60 (Monaco et al, 2010(Monaco et al, , 2011Calzolari et al, 2010;Savini et al, 2012, 61 2013) and several human cases were reported (Calistri et al,62 2010a; Rizzo et al, 2009Rizzo et al, , 2012Bagnarelli et al, 2011;Delbue 63 et al, 2014). USUV was first reported in Austria in 2001 when a 64 considerable die-off of Eurasian blackbirds (Turdus merula) was 65 observed in and around Vienna, but a recent retrospective analysis 66 of archived samples from death birds in the Tuscany region (Italy) 67 in 1996 provided evidence for an earlier introduction into Europe 68 (Weissenböck et al, 2002(Weissenböck et al, , 2013.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In order to monitor and control WNV 55 circulation, a serological, entomological and virological surveil-56 lance program for West Nile neuroinvasive disease has been imple-57 mented at the national level by the Italian Ministry of Health 58 (Italian Ministry of Health, 2008). Within this framework it was 59 possible to detect viral circulation in birds, mosquitoes and equids 60 (Monaco et al, 2010(Monaco et al, , 2011Calzolari et al, 2010;Savini et al, 2012, 61 2013) and several human cases were reported (Calistri et al,62 2010a; Rizzo et al, 2009Rizzo et al, , 2012Bagnarelli et al, 2011;Delbue 63 et al, 2014). USUV was first reported in Austria in 2001 when a 64 considerable die-off of Eurasian blackbirds (Turdus merula) was 65 observed in and around Vienna, but a recent retrospective analysis 66 of archived samples from death birds in the Tuscany region (Italy) 67 in 1996 provided evidence for an earlier introduction into Europe 68 (Weissenböck et al, 2002(Weissenböck et al, , 2013.…”
mentioning
confidence: 94%
“…WNV appeared for the first time 51 in Italy in 1998 causing encephalitis in horses in Tuscany 52 (Autorino et al, 2002). Ten years later, WNV reappeared in north-53 ern Italy affecting horses and humans (Calistri et al, 2010a,b;54 Monaco et al, 2010Monaco et al, , 2011. In order to monitor and control WNV 55 circulation, a serological, entomological and virological surveil-56 lance program for West Nile neuroinvasive disease has been imple-57 mented at the national level by the Italian Ministry of Health 58 (Italian Ministry of Health, 2008).…”
mentioning
confidence: 98%
“…Analysis of the circulating virus has shown that it was genetically closely related to the virus that emerged in Hungary in 2004 [158] . An increasing activity of WNV in horses has also been observed lately in Europe [156,159,160] , including a large outbreak that took place in northeast Italy in 2008 involving 251 stables with 794 cases and 5 deaths [156,161] . At the same time, nine human cases of West Nile fever (WNF) were reported in the area [161] .…”
Section: Europe and The Mediterranean Basinmentioning
confidence: 99%
“…An increasing activity of WNV in horses has also been observed lately in Europe [156,159,160] , including a large outbreak that took place in northeast Italy in 2008 involving 251 stables with 794 cases and 5 deaths [156,161] . At the same time, nine human cases of West Nile fever (WNF) were reported in the area [161] . In southern Spain, during summer 2010, the first outbreaks of severe WND in horses were reported with 41 diagnosed cases and 10 deaths, and 2 laboratory confirmed human cases (http://www.oie.int/wahis/).…”
Section: Europe and The Mediterranean Basinmentioning
confidence: 99%
“…In total, 67 equine outbreaks with 128 cases distributed in Sicilia, Veneto, Molise, and Emilia Romagna were confirmed. The surveillance plan enabled the identification of 6 human cases of WND [25,26,27].…”
mentioning
confidence: 99%